“El proyecto Riobamba digital y su incidencia en la opinión pública de los habitantes de las parroquias urbanas del cantón Riobamba comprendida entre 15 a 30 años de edad, en el período junio-diciembre de 2015”. - Agreda Tandazo, Orlando Ismael (2016)
The "Riobamba Digital" project and its impact on the public opinion of the inhabitants of the urban parishes of the canton Riobamba, between 15-30 years of age, in the period June-December 2015. ABSTRACT: The present research project had as an objective to determine the incidence of “Riobamba Digital Project”, in the public opinion of the habitants of urban areas of the Riobamba canton, comprehended between 15 to 30 years old, in the period June - December 2015; it was described the problem statement, the problem formulation, the general objective, the specific objectives, the justification and importance of the topic, being these the basic guidelines in which this research project was guided. For that effect, it was done in first place an analytic synthetic research, through it was investigated in the theorical frameworks the principal currents according the public opinion and digital cities. Also, it was done the exploratory study for gathering information through surveys in the citizenship, that was segmented for the study and finally it was determined through the results that 55 % of the people use the resources of the “Riobamba Digital Project” for that reason it was proved its incidence inside the public opinion. In conclusion, it was determined that the “Riobamba Digital Project” has a big rating of the acceptance by the urban population of Riobamba canton, but the GADMR need to generate better mechanisms to promulgate the use and benefices of the project, as well as the implementation of adequate equipment to improve the connectivity, for in this way obtain to satisfy the necessities of the users.